An architecture design for smart E-waste management system / Siti Feirusz Ahmad Fesol, Mohd Norikhmal Hishyam Makimin and Raihah Aminuddin - Ahmad Fesol, Siti Feirusz; Makimin, Mohd Norikhmal Hishyam; Aminuddin, Raihah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
E-waste is an uncommon topic to be discussed nowadays due to the need for more awareness regarding this topic among people. Although there are already several establishments of e-waste collection centers, there still needs to be more awareness among the public on proper e-waste handling. Based on this urgency, this study aims to propose a model of an architecture design for designing a Smart E-waste Management System using the Haversine algorithm. This system will work as a medium to disseminate information, create awareness, and educate the public about e-waste and how it would bring harm to humans and the environment if not handled properly. The results of this study present the use case, flowchart, and the final interface of the proposed system. In the future, the proposed system can be improved in terms of the accuracy of the location markers and able to provide real-time updates based on location-based data.